The handoff process for 3rd generation mobile system - Jane ak., Motal (University Malaysia Sarawak, UNIMAS., 2004)
The third generation of mobile communication system will include the multimedia application together with voice and data. Basically, this project will investigate about the efficient handoff control process for the 3G mobile system. In this research this third generation networks are referred to as UMTS (Universal Mobile Telecommunications Systems).